Empowerment of Tidung Island Coastal Communities through Language Toward Tourism Resilience - Kaprisma, Hendra (Makara Human Behavior Studies in Asia, 2022)
Over 60% of Indonesian people live in coastal areas, which is a figure that escalates yearly. Thus, the government must prioritize the development of the marine sector on the Indonesian coast. As modernization and globalization progress, the wealth of the coastal culture should be preserved and cultivated as an identity or national pride symbol. The lack of educational factors such as foreign language skills prevents coastal communities from maximizing their territory’s potential. This study was conducted by employing the curriculum-based measurement approach on the coastal communities of Tidung Island. This approach was used to support foreign language learning activities on Tidung Island. The research on foreign language learning can contribute to increasing the local culture’s potential and enhancing the resilience of tourism on Tidung Island. Results show that age and prior knowledge of foreign languages affect the learning ability of Tidung Island locals. Foreign languages with a similar alphabetical script and phonology to the Indonesian language are easier for locals to learn. Learning new vocabulary and phrases related to tourism and hospitality can facilitate global tourism in Tidung Island.